PENGARUH FAKTOR FUNDAMENTAL TERHADAP RETURN SAHAM PERUSAHAAN CONSUMER GOODS - Parlindungan, Juliaster; Maghfiroh, Siti; Faturokhman, Agus (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2022)
This research is a type of quantitive research in analyzing the fundamental effect on stock returns of consumer goods companies on the Indonesia Stock Exchange. The purpose of this study is to determine the effect of debt to equity ratio, cash ratio, net profit margin, and total asset turnover on stock returns. The population in this study are consumer goods companies listed on the Indonesia Stock Exchange for the period 2015-2019. This study uses judgemental sampling techniques and obtains as many as 15 companies or 75 company financial statements for the periode 2015-2019 as samples. Based on the results of the analysis that has been carried out using IBM SPSS Software v25 the results are: (1) debt to equity ratio has a negative and significant effect on stock returns, (2) cash ratio has no effect on stock retruns, (3) net profit margin has a positive effect and significant effect on stock returns, (4) total asset turnover has a positive and significant effect on stock returns, (5) total asset turnover is the most dominant independent variable on stock return. The implication of the conclusion above is that investors can be more careful in choosing the stocks they want to buy by considering the fundamentals of the company first. The company is obliged to maintain the company's fundamentals properly so that investors and related parties can see it well.